The Effect of Organizational Culture and Work Motivation on Teacher’s Performance - Yusnita, Weni Emelda; Fitria, Happy; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2022)
This study examined the organizational culture and work motivation on teacher’s performance. This study used qualitative method. The data were collected using questionnaire and documentation. The results showed organizational culture and teacher’s motivation partially and together have a significant effect on the performance of SMA Negeri 1 Belimbing teachers. This study states to focus the organizational culture and work motivation in order to achieve good teacher’s performance.